Early Childhood Teacher’s Self Regulated Strategy in Digital Environment: A Preliminary Investigation in Indonesia - Andrisyah Andrisyah; Rohmalina Rohmalina; Bayu Rima Aditya; Elis Hernawati; Aditya Permadi (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This study aims to investigate the self-regulated strategy of early childhood teachers in online learning during the Covid-19 pandemic. A quantitative survey approach was used as a method in this study. The data collection involved 100 early childhood teachers in Indonesia with a focus on the analysis of six dimensions of self-regulated strategy (1) goal setting, (2) environment structuring, (3) task strategies, (4) time management, (5) help-seeking, and (6) self-evaluation. The results of this study indicated that the level of self-regulated of early childhood teachers in a digital environment is good with an average value of 82.025%. In addition, the research findings also confirmed that the Covid-19 pandemic has not dampened the enthusiasm of early childhood teachers to adaptive in the digital learning environment. The main contribution of this study is to provide an understanding of the importance of self-regulated strategy for early childhood teachers in a digital environment. The results of this study can be useful for the Indonesian early childhood directorate as a basis for policy making and evaluating the improvement of the competence of early childhood teachers in Indonesia.Abstrak: Penelitian ini bertujuan untuk mengetahui strategi self-regulated guru PAUD dalam pembelajaran online di masa pandemi Covid-19. Pendekatan survei kuantitatif digunakan sebagai metode dalam penelitian ini. Pengumpulan data melibatkan 100 guru PAUD di Indonesia dengan fokus pada analisis enam dimensi strategi self-regulated, yakni (1) penetapan tujuan, (2) penataan lingkungan, (3) strategi tugas, (4) manajemen waktu, (5) bantuan, dan (6) evaluasi diri. Hasil penelitian ini menunjukkan bahwa tingkat self-regulated guru PAUD di lingkungan digital sudah baik dengan nilai rata-rata 82,025%. Selain itu, temuan penelitian juga menegaskan bahwa pandemi Covid-19 tidak menyurutkan semangat guru PAUD untuk beradaptasi di lingkungan pembelajaran digital. Kontribusi utama dari penelitian ini adalah untuk memberikan pemahaman tentang pentingnya strategi self-regulated bagi guru PAUD di lingkungan digital. Hasil penelitian ini dapat bermanfaat bagi Direktorat PAUD Indonesia sebagai dasar pengambilan kebijakan dan evaluasi peningkatan kompetensi guru PAUD di Indonesia.